CHALLENGES AND SUCCESS FACTORS OF LEAN TRANSFORMATION IN HIGHER EDUCATION INSTITUTIONS: A COMPREHENSIVE DOCTORAL THESIS - Abduraxmonova Fotima Odilbayevna (Prospects for innovative technologies in science and education, 2026)
This doctoral thesis presents an exhaustive investigation into the challenges and critical success factors governing Lean transformation across UK higher education institutions (HEIs), contributing original empirical insights through University of Warwick's pioneering Central Registry implementation. Grounded in a sophisticated mixed-methods architecture integrating PRISMA 2020 systematic literature review (2,847 records refined to 28 high-evidence sources), longitudinal case study analysis (n=28,000 students, 420 staff across 24 months), and comparative benchmarking against global exemplars (St Andrews, LeanUnivers Morocco, Cardiff Metropolitan), the research systematically dissects entrenched barriers including academic culture resistance (prevalence 68%, effect size d=1.42), legacy process complexity (72% non-value activity ratio), faculty identity threat (54% resistance index), and institutional inertia rooted in dual research-teaching logics.